Analysis Of Customer Satisfaction On The Application Of The Covid-19 Protocol At The Inter-City Bus Terminal - Irfan Rifai, Andri; Fazadi Rafianda, Dimar; Isradi, Muhammad; Mufhidin, Amar (International Journal of Engineering, Science and Information Technology, 2021)
The rise of the Covid-19 outbreak in Indonesia, especially Bekasi City, it is very strong  influencing the existing regulations at the Bekasi city main terminal the author wants to research  customer satisfaction with the facilities and implementation of the Covid-19 protocol at terminal bus in Bekasi City. This study aims to describe the perception of satisfaction  customers using a questionnaire against health protocols in terminal facilities  in the terminal main bus Bekasi. This method is carried out by direct survey to the  location  research in order to obtain data on existing facilities. Then also with distributed questionnaires to 90 respondent. The population taken in the study  these are customers at the Bekasi City Main Terminal. The data processed in this study uses Microsoft Excel and SPSS versions 24 and 16 with method  used by Importance Performance Analysis (IPA). It was found that the performance level  facilities and customer satisfaction that must be considered in A Quadrant.  The main priority is for smoking prohibition, drainage, special access  pedestrians / passengers with special needs, luggage storage, charging station, and the facilities for a nursing room.